HEAT EXCHANGE IN SLOT-HOLE RECUPERATORS - L. E. Rovin; L. N. Rusaja (Литьë и металлургия, 2014)
At calculation of slot heat exchangers it is necessary to take into account the additional stream of heat transferred by emission from internal wall to an external one and further distributed between heated air and environment.